Investigating the High Electron Mobilities and Transport Scattering Processes in 2D Non‐Van Der Waals Bi 2 O 2 Te Nanosheet Films - Sasithorn Chomngam; Samuk Pimanpang; Chesta Ruttanapun; Nopporn Rujisamphan; Anusit Thongnum (Advanced Theory and Simulations, 2025)
Abstract Bismuth oxytelluride (Bi 2 O 2 Te) nanosheets, a 2D non‐van der Waals (2D‐nvdW) semiconductor, has exceptionally high carrier mobilities, between 496 and 584 cm 2 V −1 s −1 at room temperature (RT). Its numerous potential applications in multifunctional electronic devices have sparked much research interest. However, comprehensive explanations of the high RT mobilities and transport scattering processes in the Bi 2 O 2 Te nanosheet films are still sought. Herein, measured mobility data, between 5000 and 54,074 cm 2 V −1 s −1 at 2 K and 125–584 cm 2 V −1 s −1 at 300 K, are examined and modeled considering several scattering sources, including ionized impurities, longitudinal optical (LO) phonon, and electron–electron interactions. The total mobility based on three scattering mechanisms provided good quantitative agreement with the experimental results from thicknesses ranging from 21.0 to 55.0 nm. Ionized impurity scattering limits mobility at temperatures lower than 50 K, but LO phonon and electron–electron scatterings dominate at temperatures between 50 and 300 K. When the thickness decreases to 21.0 nm, electron‐electron scattering strength becomes stronger and the RT mobility drops to 125 cm 2 V −1 s −1 . These findings advance the knowledge of the charge transport mechanisms that underlie the Bi 2 O 2 Te nanosheet and provide more details for other 2D‐nvdW and 2D semiconductors.
Keywords: 2D Materials and Applications; Topological Materials and Phenomena; Advanced Thermoelectric Materials and Devices